Valuation of Shariah Compliant Stocks Using the DCF Technique : Evidence from India - Irfan, Mohammad; Akhtar, Asif (Indian Journal of Research in Capital Markets, 2016)
Shariah compliant stocks are ethical and faith-based companies. There is a myth that Islamic finance is philanthropy, but Shariah is a canonical law, which the observant Muslims adhere to in their daily lives. Basically, Islamic stock indices are subsets of conventional benchmarks that include only those companies which qualify the Shariah Index screening on the basis of sectoral and financial screening. The main objective of this study was to estimate the valuation of Shariah compliant companies, which are listed on the S&P BSE 500 Shariah. There are 10 sectors working in the Shariah Index. There are ten select companies, one company from selected sectors. Selected 'A' category companies were taken for the study and the time period of the study is from January 2010 to December 2014. Various models for valuation were applied for the analysis, which includes: Beta (CAPM), FCFE Model, t-test, and so forth. The results of the study explained the significant relation between intrinsic value and market value of shares. The relationship is supported to FCFE of Shariah compliant stocks. DCF is a valuation method used to approximate the fruitfulness of an investment opportunity for the future. Shariah compliant stocks are continuously growing in the capital markets of India. The recorded growth has proven that Shariah investments are not only favorable for religious values, but also lead to the economic growth of a nation.